149k views
5 votes
How do you solve for m?

m= −(4+m)+2

User Yorkw
by
3.9k points

2 Answers

2 votes
m= -(4+m)+2
m= -4-m+2
2m= -2
m= -1

Hope it helps : )
User Jatin Dhoot
by
5.6k points
4 votes

Answer:


\bf m = - 1

Explanation:


\bf m= −(4+m)+2

First of all, let's Rearrange the given terms :-


\bf m = - ( m +4) + 2

Now, let's distribute:-


\bf m = - m - 4 + 2

Add numbers -4 + 2 = -2


\bf m = - m - 2

Add m to both sides, and combine like terms :-


\bf 2m = - 2

Divide both sides by 2 :-


\bf m = - 1

User Shubham Arora
by
5.1k points